2022
DOI: 10.1021/acsami.1c21729
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Nanomedicine to Enhance the Efficacy of Adjuvant Radiotherapy for Treating Osteosarcoma

Abstract: It is vital to remove residual tumor cells after resection to avoid the recurrence and metastasis of osteosarcoma. In this study, a mineral nanomedicine, europium-doped calcium fluoride (CaF 2 :Eu) nanoparticles (NPs), is developed to enhance the efficacy of adjuvant radiotherapy (i.e., surgical resection followed by radiotherapy) for tumor cell growth and metastasis of osteosarcoma. In vitro studies show that CaF 2 :Eu NPs (200 μg/ mL) exert osteosarcoma cell (143B)-selective toxicity and migration-inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Wang et al first found that CaF 2 NPs may be selectively toxic to tumor cells. They developed a europium (Eu)-doped CaF 2 NPs to inhibit the growth and migration of osteosarcoma [ 98 ]. Moreover, CaF 2 material can increase cell adhesion and inhibit tumor metastasis and cooperate with Eu to inhibit the recurrence and metastasis of residual tumor cells.…”
Section: Classification and Physicochemical Properties Of Calcium Com...mentioning
confidence: 99%
“…Wang et al first found that CaF 2 NPs may be selectively toxic to tumor cells. They developed a europium (Eu)-doped CaF 2 NPs to inhibit the growth and migration of osteosarcoma [ 98 ]. Moreover, CaF 2 material can increase cell adhesion and inhibit tumor metastasis and cooperate with Eu to inhibit the recurrence and metastasis of residual tumor cells.…”
Section: Classification and Physicochemical Properties Of Calcium Com...mentioning
confidence: 99%
“…The percentage of 4T1 cells at the G2/M phase was higher for UM (15.0%) than that in the PBS group (6.6%, Figure B). Compared with other phases, cells in the G2/M phase have the highest sensitivity in response to radiation. We hypothesized that more UM pretreated cells would die under X-ray irradiation. As shown in Figure A,C, at a given concentration of 100 μg/mL and subsequent X-ray irradiation at 4 Gy, the 4T1 cell viability decreased dramatically from 91.0% for UiO to 15.7% for UM, which was even 20.7% lower than the predicted cell viability, certifying that the response of 4T1 cells to X-ray was boosted upon UM pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…CaP TiO 2 @CaP Ca 2+ overload, SDT [155] lipid-CaP-Cu 2+ -disulfiram (DSF)(Cu-LCP/DSF NPs) CaP as nanocarrier, ICD [62] CaBPs Ca 2+ overload, changing the osmotic pressure [156] Fe/Se-CaP Boost adaptive immune response [113] CM@CaP NGs Increase the delivery and uptake efficiency of antigens, induce immune responses [27] OMV@CaP Neutralize tumour acidity, M2-to-M1 polarization [123] CaS ZnPP@PAA-CaS Ca 2+ overload, tumour calcification, induce ICD [71] CaF 2 CaF 2 Ca 2+ overload, peroxidase (POD)-mimicking activity by generating ROS [76] CaF 2 :Eu NPs Carrier, scintillator, Ca 2+ -induced radiosensitization [157] Compared to traditional therapies that use drugs to control Ca 2+ levels, these burgeoning nanoplatform-based strategies for regulating Ca 2+ homeostasis have several advantages. Firstly, nanomaterials can be precisely targeted to reduce the adverse effects of Ca 2+ on normal cells and tissues.…”
Section: Host Materials Namementioning
confidence: 99%